Linker, loading, and reaction scale influence automated glycan assembly - Dal Colle, Marlene C. S.; Ricardo, Manuel G.; Hribernik, Nives; Danglad-Flores, José; Seeberger, Peter H.; Delbianco, Martina (Beilstein Journal of Organic Chemistry, 2023)
Automated glycan assembly (AGA) affords collections of well-defined glycans in a short amount of time. We systematically analyzed how parameters connected to the solid support affect the AGA outcome for three different glycan sequences. We showed that, while loading and reaction scale did not significantly influence the AGA outcome, the chemical nature of the linker dramatically altered the isolated yields. We identified that the major determinants of AGA yields are cleavage from the solid support and post-AGA purification steps.
Keywords: automated glycan assembly; photocleavable linker; polysaccharides; solid-phase synthesis